Implementation of the Importance Performance Analysis Method in Measuring the Level of Community Satisfaction with Service Performance - Haumetan, Efrida_R; Nababan, Darsono (Yayasan Kita Menulis, 2022)
Service can be said to be satisfactory, if the service can meet community satisfaction. A satisfaction is achieved if the service received by the community is in accordance with what is expected. To determine the level of community satisfaction with service performance at the Department of Population and Civil Registration, North Central Timor Districts, it is necessary to have a system to measure the level of community satisfaction. The measurement of community satisfaction is carried out using the Importance Performance Analysis (IPA) method which considers the level of interest or expectations of the respondents, with indicators or dimensions in the form of physical tangibles, reliability, responsiveness, assurance, and empathy. The result of this research is the construction of a website-based Measurement System that is able to determine the level of community satisfaction with the performance of the services provided. Measurement using the IPA method, obtained performance that must be improved or reduced based on its quadrant mapping with 25 attributes, which are divided into 4 quadrants, namely quadrant I (main priority) 8attributes, quadrant II (maintain achievement) 3 attributes, quadrant III (low priority) 3 attributes, and quadrant IV (excessive) 11 attributes.